“Just a couple of queer fish”: The queer possibilities of Rita Mae Brown’s Rubyfruit Jungle - Lorig, Josette (Contemporary Women's Writing, 2021)
Rita Mae Brown’s Rubyfruit Jungle (1973) is a foundational work of lesbian literature and has been characterized as a queer text. This essay begins with resistance to reading the novel as a wholly celebratory queer text because of how it positions a form of essentialized lesbianism against queer sexualities that are coded as deviant and abnormal. Nonetheless, Rubyfruit Jungle brims with queer narratives, queer scenes, and queer characters. In the essay’s second half, I draw on Eve Kosofsky Sedgwick’s model of reparative reading to engage with potential queer readings the novel affords. I show how readers can recuperate the queer sexualities the novel documents in ways that the novel – with its specific historical and political positionality – did not or could not account for.
Keywords: amériques; approches et analyses; arts; discipline; discours dominant; identités LGBTQIA2+; personnes lesbiennes; queer; ressource en ligne; régions géographiques; systèmes d'oppressions; états-unis; études littéraires